Latin American artists of the twentieth century a selection from the exhibition = Artistas latinoamericanos del siglo XX : selecciones de la exposición. - Museum of Modern Art (New York, N.Y.). (New York Museum of Modern Art Distributed by Harry N. Abrams, Inc., Publishers, 1993)
After years of neglect by cultural institutions in the United States and Europe, Latin American art, during the past decade, has been the subject of several large exhibition surveys, as well as represented by retrospectives of individual artists. The present exhibition is in several ways perhaps the most ambitious of these efforts, as it represents the works of more than ninety artists with nearly three hundred works, beginning in 1914, with the first generation of early modernists, and extending to young contemporary artists, including Latino artists working in the United States today.

It is particularly appropriate that the exhibition be shown at the Museum of Modern Art in New York, because this museum was the first institution outside Latin America to collect and exhibit the work of Latin American artists, beginning with an exhibition by the Mexican master Diego Rivera in 1931, two years after the Museum's founding. The first work by the Latin American artist to enter the Museum's collection was Abby Aldrich Rockefeller's 1935 gift of Jose Clemente Orozco's Subway.
"Published on the occasion of the exhibition 'Latin American Artists of the Twentieth Century' at the Museum of Modern Art, New York, June 6-September 7, 1993"--Colophon.
English and Spanish
Keywords: Art, Latin American -- 20th century -- Exhibitions